2016
DOI: 10.4028/www.scientific.net/ssp.257.175
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding Specifics of Hybrid Metal-Polymer Nanocomposites Based on Cobalt Nanoparticles and Polyacrylonitrile: X-Ray Spectroscopy Investigation

Abstract: The cobalt-containing polyacrylonitrile (PAN) films were fabricated using IR-pyrolysis under low vacuum conditions. It was found that Co/PAN films have a porous structure and cobalt nanoparticles with size 0.1-0.2 μm embedded into PAN matrix. Besides, as a result of interaction between PAN matrix and Co ions unsaturation in the polymer backbone is observed caused by the transformation of the C≡N triple bond to a C=N double bond. At the same time formation of Co-N bond is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Advantage of PAN-based material is the possibility of obtaining films with functional properties and there is no need to use complex technological equipment. Thin cadmium-containing PAN films (h = 0.09 µm -0.17 µm) with a resistance of 7·10 8 to 3·10 10 Ω were obtained by pyrolysis method. It has been found that the temperature dependence of the resistance of the films has an exponential character.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantage of PAN-based material is the possibility of obtaining films with functional properties and there is no need to use complex technological equipment. Thin cadmium-containing PAN films (h = 0.09 µm -0.17 µm) with a resistance of 7·10 8 to 3·10 10 Ω were obtained by pyrolysis method. It has been found that the temperature dependence of the resistance of the films has an exponential character.…”
Section: Resultsmentioning
confidence: 99%
“…The technology of fabrication gas sensitive PAN films that does not require high-tech equipment and the ability to exhibit gas-sensing properties at room temperatures opens the prospect of creating flexible sensors. The gas-sensitive metal-containing PAN thin films have been fabricated [6] that are sensors for detecting to CO, NO2, Cl2, NH3, H2S [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%